2020
DOI: 10.3390/plants9111607
|View full text |Cite
|
Sign up to set email alerts
|

Gene Mapping, Genome-Wide Transcriptome Analysis, and WGCNA Reveals the Molecular Mechanism for Triggering Programmed Cell Death in Rice Mutant pir1

Abstract: Programmed cell death (PCD) is involved in plant growth and development and in resistance to biotic and abiotic stress. To understand the molecular mechanism that triggers PCD, phenotypic and physiological analysis was conducted using the first three leaves of mutant rice PCD-induced-resistance 1(pir1) and its wild-type ZJ22. The 2nd and 3rd leaves of pir1 had a lesion mimic phenotype, which was shown to be an expression of PCD induced by H2O2-accumulation. The PIR1 gene was mapped in a 498 kb-interval between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 88 publications
1
10
0
Order By: Relevance
“…This suggests that PCD mechanism plays a vital role in inducing seedless fruits. In rice, up-regulation of lignin biosynthesis genes, including 4CL, resulted in an increased content of lignin and led to activate PCD ( Chen et al, 2020 ). It was also reported that overexpression of OsAAE3 , which encodes a 4CL like protein, can lead to PCD, which contributed to the repressing of floral development and decreased fertility rate of the anther ( Liu et al, 2017a ).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that PCD mechanism plays a vital role in inducing seedless fruits. In rice, up-regulation of lignin biosynthesis genes, including 4CL, resulted in an increased content of lignin and led to activate PCD ( Chen et al, 2020 ). It was also reported that overexpression of OsAAE3 , which encodes a 4CL like protein, can lead to PCD, which contributed to the repressing of floral development and decreased fertility rate of the anther ( Liu et al, 2017a ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, bursts of production of NO and ROS usually occur very early in the defense response and are often important for the initiation of hypersensitive response, together with lipid peroxidation, transcriptional reprogramming, ion fluxes and cell wall fortification [ 31 ]. We suggest that our findings about OsAAP3 in cell death and lesion mimic in rice leaves are linked to the hypersensitive response, like some mutants display hypersensitive response-like lesion in the absence of pathogens attacks [ 11 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that overexpression of lignin synthesis enzyme gene OsAAE3 leads to an increase in H 2 O 2 content, which triggers PCD induced by ROS [ 36 ]. Recently, a mutant pir1 showed that the spontaneous lesions mimic phenotype is caused by PCD in the mutant leaves [ 32 ]. And KEGG analysis revealed that DEGs were most highly enriched in phenylpropanoid biosynthesis [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weighted gene co-expression network analysis (WGCNA) is an effective tool to identify co-expressed modules and hub genes 27 , which has been applied in various plants including Camellia sinensis 28 , hot peppers 29 , rice 30 and wheat 27 to explore various abiotic stresses response molecular mechanisms. It is a signi cant way to understand gene function and association from the trancriptome-wide [31][32][33] . However, there is no previous report of using WGCNA to identify shade response hub genes in M. sinostellata.…”
Section: Introductionmentioning
confidence: 99%